Влияние обрастаний эпибионтными водорослями наружных покровов голых жаброногов (Crustacea, Anostraca) - Вехов, Н.В.; Вехова, Т.П. (Вестник зоологии, 1993)
Results of study of Polyartemia forcipata overgrowing in mountain-tundra lakes in Polar Urals in June—August 198. Epibiont algae overgrowing specific composition, their distribution over Polyartemia cover, influence on behaviour and reproduction are given.